2014
DOI: 10.4028/www.scientific.net/amr.910.262
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Effectiveness and Manufacture Technique of Functional Metal Composite Knitted Fabrics

Abstract: In order to fabricate fabrics with electromagnetic shielding effectiveness (EMSE) and other function, we fabricated Crisscross-section polyester /antibacterial nylon / stainless steel wires (CSP/AN/SSW) composite yarns with stainless wires as core yarn, antibacterial nylon and crisscross-section polyester as inner and out wrapped yarns, respectively. Knitted fabrics were fabricated with the metal composite yarns with wrap amount of 8 turns/cm on a circular knitted machine. Furthermore, the EMSE of the metal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Due to their low density, great electrical conductivity, ease of modification, and high chemical stability, carbon materials have increasingly replaced metal materials in the area of electromagnetic shielding during the last several decades. Among carbon materials, carbon foam has a tunable three-dimensional network cell structure: a material with low weight, a broad absorption frequency, and specific structural and functional properties [1][2][3][4]; therefore, it has been highly desired by researchers. The majority of research has shown that differences in the cell structure of carbon foam [5] have a large influence on its electromagnetic shielding performance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low density, great electrical conductivity, ease of modification, and high chemical stability, carbon materials have increasingly replaced metal materials in the area of electromagnetic shielding during the last several decades. Among carbon materials, carbon foam has a tunable three-dimensional network cell structure: a material with low weight, a broad absorption frequency, and specific structural and functional properties [1][2][3][4]; therefore, it has been highly desired by researchers. The majority of research has shown that differences in the cell structure of carbon foam [5] have a large influence on its electromagnetic shielding performance.…”
Section: Introductionmentioning
confidence: 99%